AN EVALUATIVE STUDY OF THE MILLENNIAL FARMERS CAPACITY DEVELOPMENT PROGRAM BY CV PENDAWA KENCANA MULTIFARM USING THE CIPPO MODEL - Rena Suryaningsih; R Hermawan; Sukadi (CV. Radja Publika, 2026)
The agricultural sector plays a strategic role in national development, particularly in ensuring food security and supporting economic sustainability. However, Indonesia is currently facing a decline in the number of agricultural actors and a regeneration crisis among farmers, especially in the younger generation. In response to this issue, various capacity-building programs for millennial farmers have been implemented, including the program conducted by CV Pendawa Kencana Multifarm. This study aims to evaluate the effectiveness of the millennial farmer capacity development program using the CIPPO evaluation model (Context, Input, Process, Product, Outcome). This research employed a descriptive quantitative approach involving 42 millennial farmer respondents selected through proportional random sampling using the Slovin formula. Data were collected using questionnaires based on a 1–5 Likert scale and analyzed using descriptive statistics and the Program Effectiveness Index (PEI) to measure each CIPPO component. The results show that the program is categorized as effective, with an overall IEP score of 86.87%. Each component also falls within the effective category, with scores of 85.19% for Context, 87.62% for Input, 88.24% for Process, 87.81% for Product, and 85.48% for Outcome. The highest effectiveness was found in the Process component, indicating strong participant engagement and effective implementation of participatory, practice-based learning. Meanwhile, the Context component recorded the lowest score, suggesting the need for improved alignment between program design and participants’ specific needs. Overall, the program has proven effective in improving participants’ knowledge, skills, and farming capacity, as well as contributing to behavioral change and farming sustainability. However, further refinement is needed in the planning stage to enhance contextual accuracy and long-term impact.